Moving enterprise resource planning (ERP) systems to the cloud: the challenge of infrastructural embeddedness - Hustad, Eli (2021)
Cloud enterprise resource planning (ERP) solutions allow organizations to support and coordinate key business processes by leveraging virtualization. Nevertheless, moving ERPs to the cloud is not straightforward, and organizational cloud ERP initiatives raise multiple concerns. We conducted an in-depth systematic review of relevant research literature and identified six key concerns related to cloud ERP implementation: a) the introduction of new ERP work arrangements, b) the migration of legacy data, c) the assurance of compliance with extant rules and regulations for security, d) the continuous alignment between ERP functionality and business processes, e) the ongoing integration between ERPs and the rest of the organization’s application portfolio, and f) the establishment of adequate reliability levels. The identified concerns are associated with both transition management and operations supported by cloud ERPs. All the identified concerns are also related to the need to achieve infrastructural embeddedness. This need sets ERPs apart from other types of cloud-based applications, such as office automation solutions that do not have as many dependencies and exchanges with other systems and repositories within an organization’s information infrastructure. We argue that the challenge of embeddedness has different implications for organizations of different sizes, and we call for further empirical research.